Climate Refugees" in a Legal Vacuum: To Develop a System of Assistance, Recognition and Compensation (International relations and international law Journal, 2022)
Climate change has become a major driver of forced displacements over the years. According to the World Bank between 20 and 200 million people will be displaced by climate disasters by 2050. Most of the “climate refugees” currently move within the borders of their own countries, however, when such migrants cross state borders, they will not be recognized as refugees according to the existing international conventions. Moreover, the inhabitants of the "sinking" island countries are at risk of becoming de facto stateless persons and, subsequently, will not be able to enjoy protection of any state. This article highlights the need for a contemporary international legal framework to address the climate refugees’ issue. The development of legal instruments to facilitate decisions on resettlement of such refugees and to define the status of environmental migrants shall be seen as an immediate, both academically and practically orientated, task. The authors analyse individual and group cases of climate-related asylum and some cases of international protection to “climate refugees” being granted within the existing legal framework. The article stresses the emergency of debating such an asylum category and of developing a corresponding system of responsibilities and compensations internationally.Keywords: climate refugees, legal framework, protection, ecological asylum, climate change